Facile usage of a MYTHEN 1K with a Huber 5021 diffractometer and angular calibration in operando experiments. Issue 4 (23rd June 2016) - Gao, Mei; Gu, Yueliang; Li, Li; Gong, Zhengliang; Gao, Xingyu; Wen, Wen
Abstract : A mechanical assembly has been successfully designed to combine a MYTHEN 1K with a point detector, and is proved facile for the angular calibration of individual pixels. In `flat‐plate transmission' geometry, which is frequently used in various operando experiments, straightforward corrections can be efficiently made to compensate for sample displacement away from the diffractometer center. Abstract : A facile usage of a MYTHEN 1K detector with a Huber 5021 six‐circle diffractometer is described in detail. A mechanical support has been custom designed for the first time to combine the MYTHEN 1K detector with a point detector, which can be used as a reference point for each individual pixel of the MYTHEN 1K during measurements. The MYTHEN 1K is mounted on the arm of the 2θ circle of the Huber diffractometer with an intrinsic angular resolution of ∼0.0038°, and its pitch angle can be automatically adjusted with an accuracy of 0.0072°. Standard procedures are discussed for its calibration. Programs have been written in the SPEC environment for simultaneous data conversion, integration and acquisition. The X‐ray powder diffraction patterns of standard samples were measured in the Debye–Scherrer geometry and matched well with those of references. The angular shift due to sample‐to‐center displacement in the `flat‐plate transmission' geometry, which is frequently employed in operando experiments, has been successfully investigated and can be efficiently corrected. One operando experiment using the MYTHEN 1K is presented. This work provides a straightforward procedure to use the MYTHEN 1K detector properly in Debye–Scherrer geometry, and could facilitate its application at other synchrotron facilities.